2019
DOI: 10.1155/2019/4396201
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Key Chemical Constituents in Processed Gastrodia elata Using UHPLC-MS/MS and Chemometric Methods

Abstract: Gastrodia elata Blume belongs to the Orchidaceae family. G. elata is often processed when used in traditional Chinese medicine (TCM). In the current study, a traditional processing method, known as “Jianchang Bang,” was applied. Steamed and dried (S&D) G. elata was processed with ginger juice for up to 5 days (GEP5D). An UHPLC-MS/MS combined with a chemometric method was developed for the analysis of processed G. elata along with the raw material as well as steamed and dried G. elata. As a result, the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…. Because p-hydroxybenzyl alcohol, which abundantly occurs in G. elata [50][51][52][53][54][55][56][57][58], is highly reactive to produce quinone methide and complex derivative via self-condensation or inter-condensation with other reactants under various conditions [86][87][88][89], this suggests that, (a) p-hydroxybenzyl alcohol is an origin of the p-hydroxybenzyl unit in the p-hydroxybenzyl-containing chemical constituents of "tian ma"; (b) alcoholic forms of the p-hydroxybenzyl-derived dimers and trimers are generable from p-hydroxybenzyl alcohol during processing and/or extracting of the drug material; and (c) the ethyl and methyl ethers were formed in the subsequent isolation procedure through contacting to the solvents EtOH and MeOH. To verify the suggestions, following experiments were performed: (a) an aqueous solution of p-hydroxybenzyl alcohol was refluxed, from which the products were isolated and structurally identified; (b) methylation and ethylation of the p-hydroxybenzyl alcohol-generating products were examined by UPLC-HRESIMS after refluxing of their MeOH and EtOH solutions; (c) the refluxed solutions of p-hydroxybenzyl alcohol in H 2 O, MeOH, and EtOH were compared by UPLC-HRESIMS analysis using the identified pure compounds as references.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations
“…. Because p-hydroxybenzyl alcohol, which abundantly occurs in G. elata [50][51][52][53][54][55][56][57][58], is highly reactive to produce quinone methide and complex derivative via self-condensation or inter-condensation with other reactants under various conditions [86][87][88][89], this suggests that, (a) p-hydroxybenzyl alcohol is an origin of the p-hydroxybenzyl unit in the p-hydroxybenzyl-containing chemical constituents of "tian ma"; (b) alcoholic forms of the p-hydroxybenzyl-derived dimers and trimers are generable from p-hydroxybenzyl alcohol during processing and/or extracting of the drug material; and (c) the ethyl and methyl ethers were formed in the subsequent isolation procedure through contacting to the solvents EtOH and MeOH. To verify the suggestions, following experiments were performed: (a) an aqueous solution of p-hydroxybenzyl alcohol was refluxed, from which the products were isolated and structurally identified; (b) methylation and ethylation of the p-hydroxybenzyl alcohol-generating products were examined by UPLC-HRESIMS after refluxing of their MeOH and EtOH solutions; (c) the refluxed solutions of p-hydroxybenzyl alcohol in H 2 O, MeOH, and EtOH were compared by UPLC-HRESIMS analysis using the identified pure compounds as references.…”
Section: Tablementioning
confidence: 99%
“…The above experiments demonstrated that the composition of the refluxed solutions of p-hydroxybenzyl alcohol are highly dependent upon the solvent and refluxing time. Because of the abundant occurrence of p-hydroxybenzyl alcohol in G. elata [50][51][52][53][54][55][56][57][58] (Fig. S233), the p-hydroxybenzyl-derived dimers and trimers from the "tian ma" extracts must be formed at least partially by refluxing of the drug materials in H 2 O, MeOH, or EtOH.…”
Section: Products From a Refluxed Aqueous Solution Of P-hydroxybenzyl Alcohol And Their Etherification With Meoh And Etohmentioning
confidence: 99%
See 2 more Smart Citations
“…During the past decades, HPLC-MS, as a new technique has been used to profile and identify the chemical in TCM due to its validity, sensitivity, and specialness [ 10 , 11 ]. Especially, UHPLC-HRMS such as UHPLC-Q-Exactive Orbitrap MS, UHPLC-Q-TOF MS, and UHPLC–LTQ-Orbitrap-MS, affording a higher and faster separation and higher resolution of mass, was a much more powerful equipment in the identification of TCM compared to traditional HPLC-MS [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%